Improving visual vocabularies: a more discriminative, representative and compact bag of visual words - Chang, Leonardo; Pérez-Suárez, Airel; Hernández-Palancar, José; Arias-Estrada, Miguel; Sucar, L. Enrique (Informatica, 2017)
In this paper, we introduce three properties and their corresponding quantitative evaluation measures to assess the ability of a visual word to represent and discriminate an object class, in the context of the BoW approach. Also, based on these properties, we propose a methodology for reducing the size of the visual vocabulary, retaining those visual words that best describe an object class. Reducing the vocabulary will provide a more reliable and compact image representation. Our proposal does not depend on the quantization method used for building the set of visual words, the feature descriptor or the weighting scheme used, which makes our approach suitable to any visual vocabulary. Throughout the experiments we show that using only the most discriminative and representative visual words obtained by our proposed methodology improves the classification performance; the best results obtained with our proposed method are statistically superior to those obtained with the entire vocabularies. In the Caltech-101 dataset, average best results outperformed the baseline by a 4.6% and 4.8% in mean classification accuracy using SVM and KNN, respectively. In the Pascal VOC 2006 dataset there was a 3.2% and 7% improvement for SVM and KNN, respectively. Furthermore, these accuracy improvements were always obtained with more compact representations. Vocabularies 10 times smaller always obtained better accuracy results than the baseline vocabularies in the Caltech-101 dataset, and in the 78.1% of the experiments on the Pascal VOCdataset.